Emergence and Future of Exsolved Materials. Issue 21 (31st March 2021) - Kousi, Kalliopi; Tang, Chenyang; Metcalfe, Ian S.; Neagu, Dragos
Abstract: Supported nanoparticle systems have received increased attention over the last decades because of their potential for high activity levels when applied to chemical conversions, although, because of their nanoscale nature, they tend to exhibit problems with long‐term durability. Over the last decade, the discovery of the so‐called exsolution concept has addressed many of these challenges and opened many other opportunities to material design by providing a relatively simple, single‐step, synthetic pathway to produce supported nanoparticles that combine high stability against agglomeration and poisoning with high activity across multiple areas of application. Here, the trends that define the development of the exsolution concept are reviewed in terms of design, functionality, tunability, and applicability. To support this, the number of studies dedicated to both fundamental and application‐related studies, as well as the types of metallic nanoparticles and host or support lattices employed, are examined. Exciting future directions of research are also highlighted. Abstract : Exsolution is an emerging method for producing highly active, durable, and tailorable supported nanoparticle systems via a simple, single‐step procedure. These materials have enabled step‐change advances across a wide range of applications including electrochemical energy conversion and heterogenous catalysis. In this review, the design principles, tuning, applications, and exciting future directions of research are critically presented.